Terrestrial Gamma Radiation Exposure in Bangka-Belitung Islands, Indonesia - Syarbaini Syarbaini; A. Setiawan (Atom Indonesia, 2015)
Bangka-Belitung is known as tin producer and it geologically contains higher concentrations of natural radionuclides than most other areas. The aim of this study was to evaluate the level of terrestrial gamma radiation in Bangka-Belitung Islands. The external gamma radiation dose rate from terrestrial gamma-rays have been measured at one meter above the ground by means of a portable gamma spectrometer at 66 survey points. The terrestrial gamma dose rates in Bangka island range from 43.67 to 511.54 nGy h-1 with a mean of 183.45 nGy h-1, while in Belitung island they range from 15.54 to 416.39 nGy h-1 with a mean of 132.60 nGy h-1. From this work, a strong correlation was found between dose rates found from in-situ radiation measurements and dose rates calculated theoretically from radioactivity contents of the soil at the same locations. Generally, Bangka-Belitung islands have higher outdoor natural gamma dose rates than the world average value of 0.058 μGy h-1 for the regions with normal background radiation specified by United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR).Received: 27 August 2014; Revised: 05 March 2015; Accepted: 30 March 2015